PREOPERATIVE EMBOLIZATION OF THE COMMON HEPATIC ARTERY IN PATIENTS WITH PANCREATIC BODY AND TAIL TUMORS INVADING THE CELIAC TRUNK - M. G. Abgaryan; E. R. Virshke; N. Е. Kudashkin (Сибирский онкологический журнал, 2016)
The purpose of the study was to evaluate the efficacy of preoperative embolization of the common hepatic artery in patients with pancreatic body and tail cancer invading the celiac trunk. Material and Methods. Twenty-two patients underwent distal subtotal pancreatectomy with resection of the celiac trunk and the common hepatic artery. Of these 22 patients, 6 underwent preoperative embolization of the common hepatic artery. Results. In spite of invasion of the celiac trunk, the hepatic arterial blood flow was completely blocked in all patients who underwent preoperative embolization of the common hepatic artery.   No complications related to endovascular intervention were found. In all cases, control angiography showed an adequate blood supply to the liver due to collateral circulation from the superior mesenteric artery. No ischemic complications were observed in postoperative period.  Conclusion. Preoperative embolization of the common hepatic artery appeared to be a safe procedure that could prevent the risk of ischemic complications in patients undergoing distal subtotal pancreatectomy with resection of the celiac trunk and the common hepatic artery without plastics.